A morphometric analysis of the circumolivary fiber bundle of the human brainstem - Brendel, Victor A.; Schmeisser, Michael J.; Schumann, Sven (Frontiers in Neuroanatomy, 2022)
The circumolivary fiber bundle (CFB) is considered to be an anatomical variation, which can be found on the surface of the human medulla oblongata. The macroscopical fiber bundle runs downwards from the anterior median fissure and the pyramid, around the inferior pole of the olive and turns upwards to reach the restiform body of the inferior cerebellar peduncle. Multiple fiber systems feed the constitution of the CFB (collateral corticospinal fibers, fibers connecting to the reticular formation, anterior external arcuate fibers). With this examination we provide a systematic analysis of the frequency of occurrence (6.14%), size and laterality of the CFB. Including all three fiber bundle parts (descending part, genu and ascending part) the left-sided sizes were increased. Likewise, the appearance of an unilateral left-sided CFB could be detected in more than 60 %. Our morphometrical analysis currently covers the largest sample of investigated brainstem sides (n=489) so far. This investigation should widen the perspective on how anatomists, neuroradiologists and neurosurgeons expect the anterolateral surface of the human medulla oblongata.